Optimal rule-of-thumb design of NiFeMo layered double hydroxide nanoflakes for highly efficient and durable overall water-splitting at large currents. Issue 38 (7th September 2022) - Inamdar, Akbar I.; Chavan, Harish S.; Seok, Jun Ho; Lee, Chi Ho; Shin, Giho; Park, Sunjung; Yeon, Seungun; Cho, Sangeun; Park, Youngsin; Shrestha, Nabeen K.; Lee, Sang Uck; Kim, Hyungsang; et al.
Abstract : Ni x Fe y Mo z layered double hydroxide (LDH) electrocatalysts fabricated via a simple hydrothermal technique for overall water splitting in an alkaline medium are reported. Abstract : Because hydrogen is an ideal energy source, electrocatalysts for water splitting that employ transition metal hydroxides rather than expensive precious metals to produce molecular hydrogen have been extensively investigated. In the present study, Ni x Fe y Mo z layered double hydroxide (LDH) electrocatalysts fabricated via a simple hydrothermal technique for overall water splitting in an alkaline medium are reported. The best-performing Ni x Fe y Mo z LDH catalysts require overpotentials of 200 and 86 mV to reach a current density of 10 mA cm −2 for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively. Theoretical analysis indicates that the Mo-rich OMo2 Fe and Fe-rich OFe3 active sites strongly activate the HER and OER, respectively. More importantly, a water electrolyzer containing the best-performing Ni x Fe y Mo z LDH catalysts as the anode and cathode is able to reach an industrially relevant current density of 1000 mA cm −2 at a cell voltage of only 2.1 V. The electrolyzer exhibits outstanding stability at very high current densities of 0.1, 0.5 and 1 A cm −2 for overall water splitting over 90 hours of continuous operation, which is superior to state-of-the-art devices based on precious metals. The overall water-splitting activity presented here demonstrates the practical potential of the proposed electrocatalysts as inexpensive options for use in water electrolyzers.